Bio-inspired robust non-iridescent structural color with self-adhesive amorphous colloidal particle arrays. Issue 8 (12th January 2018) - Liu, Panmiao; Chen, Jialun; Zhang, Zexi; Xie, Zhuoying; Du, Xin; Gu, Zhongze
Abstract : Bio-inspired robust non-iridescent structural color materials were fabricated from amorphous colloidal arrays of polydopamine coated silica nanoparticles through a "spraying" process. Abstract : Here we propose a new method for constructing highly color fast non-iridescent structural color materials by assembling self-adhesive poly-dopamine coated SiO2 nanoparticles (PDA@SiO2 ) for amorphous colloidal arrays through a "spraying" process. Simply by alkaline vapor treatment, the adhesive forces and fastness of the amorphous colloidal arrays were significantly improved. This was demonstrated by lap shear tests of tape tearing and cohesive failure as well as a series of fastness tests like sandpaper abrasion, finger wiping and ultrasonic cleaning. Besides, the strengthening fastness reaction could occur on different substrates, including glass, metals, polymers and paper, regardless of their chemical and physical properties. Moreover, the structural color of the PDA@SiO2 arrays was bright due to the broadband absorption of PDA, and was tunable according to the size, PDA content and arrangement of the PDA@SiO2 arrays.